1975
DOI: 10.1038/bjc.1975.232
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal studies of cell mediated immune reactions to autologous tumour antigens in patients with operable mammary carcinoma

Abstract: Summary.-The leucocyte migration and guinea-pig macrophage migration procedures were used to assess cell mediated, tumour directed immune reactions in patients with mammary carcinoma undergoing simple mastectomy with or without post-operative irradiation. Forty-seven per cent of patients reacted to autologous tumour antigens and 40o% to allogeneic antigens when tested 7 days after operation; 23% reacted to autologous antigens at 2 months, 19% at 6 months and 34%0 at 1 year after surgery. Reactions to benign ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
12
0

Year Published

1976
1976
1983
1983

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…We (Jones and Turnbull, 1975). McCoy et al (1974) have improved still further on our rate of approximately 5000 patients positive at 7 days after simple mastectomy: using 3M KCI extracts of breast tumours, significant leucocyte migration inhibition was obtained in 20/26 (770o) pre-or immediately postsurgery breast cancer patients.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…We (Jones and Turnbull, 1975). McCoy et al (1974) have improved still further on our rate of approximately 5000 patients positive at 7 days after simple mastectomy: using 3M KCI extracts of breast tumours, significant leucocyte migration inhibition was obtained in 20/26 (770o) pre-or immediately postsurgery breast cancer patients.…”
Section: Discussionmentioning
confidence: 96%
“…It was previously shown that serial postoperative measurements of tumourdirected leucocyte migration inhibition in breast cancer patients may be of relevance to the understanding of the complex host-tumour interrelationship and may provide information of clinical significance (Jones and Turnbull, 1975;Jones et al, 1976). This paper has tried to confirm that the in vitro response to particulate tumour-derived antigenic material is mediated by cellular immune mechanisms and thus permit interpretation of the clinical correlations observed in breast cancer patients.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations